Deflection of flat slab-drop panel in the G2 building at Warmadewa University - I Made Nova Hartawan; Maulana Nyoman Parthin Indra; I Nengah Sinarta I Nengah Sinarta; Triswandana I Wayan Gde Erick; Sarassantika I Putu Ellsa (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2023)
To conserve building height, flat slabs are concrete structures that do not employ beams as weight transfer to columns. The flat slab system structure is prone to shear collapse due to the lack of beams. A column head is made to forward the load from the plate to the column so that the shear value in the building is not too high. This is done by expansion at the end of the column or by thickening around the critical circumference of the column and plate meeting. The Warmadewa University G2 Building Planning Analysis is carried out during the planning stage, using a flat slab-drop panel structural system as one of the optional structural systems that can be used to obtain a building height that is in accordance with Bali Provincial Regulation Number 16 of 2009 concerning the regional spatial plan of the Province of Bali. Terompong street No. 24, Sumerta Kelod, East Denpasar sub-district, Denpasar City, Bali, is where the Warmadewa University G2 building will be built. According to the soil data, the building is constructed on a medium soil site class with a building structure risk level IV. The Warmadewa University G2 Building structure was studied using etabs v.18 software in accordance with SNI 2847-2019 requirements for structural concrete for building buildings and loading in accordance with SNI 1727-2020 criteria. The biggest deflection value occurs in the middle lane due to the load from the function room, as determined by the study for the dimensions of the 350mm thick drop panel and 250mm thick slab utilizing a column size of 600 x 600 mm with a span of 8000mm. The inner drop panel experiences the highest lateral loads due to shear failure.